Disentangling the compact city drivers and pressures: Barcelona as a case study. Issue 5 (20th October 2018) - Adelfio, Marco; Kain, Jaan-Henrik; Thuvander, Liane; Stenberg, Jenny
ABSTRACT: The compact city is globally acknowledged as the most adequate urban model to encourage sustainable urban development. Its validity is often assumed, despite the lack of clarity on what such compactness entails. The knowledge gap is even wider regarding how different drivers and pressures influence the development of more compact cities. Therefore, the authors analyse indirect and underlying processes (drivers) and more direct events, actions, and processes (pressures) affecting compact city development. Since compact city driving forces are extensively influenced by local situations, their research focused on district-level case studies within the compact city of Barcelona Municipality. Mixed methods were used, and the authors used both qualitative and quantitative data. The results revealed that drivers and pressures can both support and counteract compact city qualities and therefore any intervention has to be tailored to local conditions. In particular, the results of the in-depth analysis of local pressures and their progression over time foster an understanding of context-related nuances, thereby shifting attention from taken-for-granted compact city qualities to the driving forces that produce beneficial compactness. The authors conclude that the diversity of drivers and pressures requires the involvement of a multiplicity of stakeholders and actors in urban planning, implementation, and management.